MENCARI PIJAKAN AZAS PENDIDIKAN KEJIJRIJAN DALAM MENGHADAPI TANTANGAN PERKEMBANGAN TEKNOLOGI - Pardjono, Pardjono (Jurnal Cakrawala Pendidikan, 2016)
The main purpose of this study is to investigate analytically some philosophies to find out what philosophy on which the vocational education is appropriately based for preparing the Indonesian live in the global and information era. The study is focused only on an idealism, realism, pragmatism, and re onstructionism as a foundation of education curriculum in general and the possibilities of adoption for Indonesian vocational education. Some recommendations are suggested as follows: it is likely that vocational education better to adopt eclectical principles derived from the principles of idealism, realism, pragmatism, and reconstructionism in order for the vocational education capable of preparing students for tommorrow living that have skins as well as capabilities in adapting their life within the changing world, beside they have propositional abilities such as high motivation, creativity, and critical thinking.